1995
DOI: 10.1128/mcb.15.8.4282
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Type 2 Preferentially Stimulates Polymerase III Transcription of Alu Elements by Relieving Repression: a Potential Role for Chromatin

Abstract: The number of Alu transcripts that accumulate in HeLa and other human cells is normally very low; however, infection with adenovirus type 5 increases the expression of Alu elements dramatically, indicating that the potential for polymerase III (pol III)-dependent Alu transcription in vivo is far greater than generally observed (B. Panning and J. R. Smiley, Mol. Cell. Biol. 13:3231-3244, 1993). In this study, we employed nuclear run-on in combination with a novel RNase H-based assay to investigate transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 48 publications
(80 reference statements)
6
55
0
1
Order By: Relevance
“…The results demonstrated that the amount of 7SL RNA was twofold higher in HIV-infected than uninfected cells, while the amount of actin mRNA decreased twofold in HIV-infected cells, resulting in a fourfold increase in the intracellular ratio of 7SL to actin mRNA upon HIV infection (Table 1). The observation that HIV-1 infection leads to a fourfold increase in pol III-driven 7SL RNA expression compared with actin mRNA levels may be consistent with findings for several other viruses that are known to affect pol III-driven gene expression (Panning and Smiley 1995;Russanova et al 1995;Gottesfeld et al 1996;Piras et al 1996).…”
supporting
confidence: 86%
“…The results demonstrated that the amount of 7SL RNA was twofold higher in HIV-infected than uninfected cells, while the amount of actin mRNA decreased twofold in HIV-infected cells, resulting in a fourfold increase in the intracellular ratio of 7SL to actin mRNA upon HIV infection (Table 1). The observation that HIV-1 infection leads to a fourfold increase in pol III-driven 7SL RNA expression compared with actin mRNA levels may be consistent with findings for several other viruses that are known to affect pol III-driven gene expression (Panning and Smiley 1995;Russanova et al 1995;Gottesfeld et al 1996;Piras et al 1996).…”
supporting
confidence: 86%
“…Having confirmed the efficacy of TSA in murine fibroblasts, we examined how a chromosomal Pol III template responds to the drug. The B2 family was chosen for this analysis, since previous studies have shown that Pol III transcription of these middle repetitive genes is heavily repressed by histones in chromatin from murine fibroblasts (6,43). Consistent with these findings, treatment with TSA produced a strong induction of B2 transcripts (Fig.…”
Section: Tsa Induces B2 Gene Expression In Vivosupporting
confidence: 66%
“…Available evidence suggests that murine SINE elements are particularly subject to this type of transcriptional control through interactions with chromatin proteins (Carey et al, 1986). Moreover, some treatments (adenoviral infection, heat shock) that have previously been shown to induce SINE transcription also modulate chromatin structure (Russanova et al, 1995;Kim et al, 2001). The activation of SINE transcription following treatment with DNA-damaging agents described in this study may be dependent on the same mechanism.…”
Section: Discussionsupporting
confidence: 55%
“…Alu elements tend to be located in areas of dense heterochromatin. Chromatin structure surrounding SINE elements may play a key role in sequestering these elements to transcriptionally silent regions of the genome (Ullu and Weiner, 1985;Carey et al, 1986;Russanova et al, 1995). Available evidence suggests that murine SINE elements are particularly subject to this type of transcriptional control through interactions with chromatin proteins (Carey et al, 1986).…”
Section: Discussionmentioning
confidence: 99%